PENERAPAN MODEL PEMBELAJARAN KOOPERATIF STAD DALAM MENINGKATKAN HASIL BELAJAR DI MTS DDI BOSALIA KABUPATEN JENEPONTO - Cora, Syarifa Bulan Daeng; Thahir, Ilyas; Ahmad; Syahid, Akhmad; Wahab, Abdul (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to improve the learning outcomes of 7th-grade students in the Akidah Akhlak (Islamic Creed and Ethics) subject through the implementation of the Student Teams Achievement Divisions (STAD) cooperative learning model at MTs DDI Bosalia, Jeneponto Regency. The study employed the Classroom Action Research (CAR) method using Kurt Lewin’s model, which consists of the stages of planning, action implementation, observation, and reflection. The research was conducted over two cycles, involving 31 students and one Akidah Akhlak teacher as subjects. Data collection techniques included observation, interviews, tests, and documentation, while research instruments consisted of learning outcome tests and student activity observation sheets. Data were analyzed quantitatively to determine average scores and percentages regarding activity and learning outcomes, and qualitatively to describe the learning process. The results indicate that the implementation of the STAD model successfully improved student activity and learning outcomes. Average learning activity increased from 56.00% in the pre-cycle stage to 60.35% in Cycle I and 85.50% in Cycle II. Meanwhile, the average student learning outcome score rose from 83.27 in Cycle I to 88.44 in Cycle II. This improvement demonstrates that instruction using the STAD model fosters a learning environment that is more active, collaborative, and participatory. Students became more enthusiastic, actively engaged in discussions, gained the confidence to ask and answer questions, and demonstrated the ability to cooperate in understanding the material. Thus, the implementation of the STAD cooperative learning model can enhance student activity and learning outcomes in the Akidah Akhlak subject for 7th-grade students at MTs DDI Bosalia, Jeneponto Regency.